1997
DOI: 10.1111/j.1539-6924.1997.tb01280.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Risk Perception: How Does Perceived Risk Respond to Risk Events?

Abstract: This paper examines the relationship between perceived risk and experience. This research addresses the processes by which people learn about risk and choose among real life prospects with associated uncertainties, risks and benefits. By comparing the impact of acute risk events with that of chronic risk events on public perception of risk during and after the events, this research focuses on the learning processes that characterize what kinds of risk events alter the perception of risk. Comparing materialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 24 publications
0
48
0
2
Order By: Relevance
“…4,5,[25][26][27] To date, at least 15 risk perception factors have been identified that have direct relevance to risk communication (see the Table). 3,4,8 These factors play a large role in determining levels of concern, worry, anger, anxiety, fear, hostility, and outrage, which in turn can significantly change attitudes and behavior.…”
Section: The Risk Perception Modelmentioning
confidence: 99%
“…4,5,[25][26][27] To date, at least 15 risk perception factors have been identified that have direct relevance to risk communication (see the Table). 3,4,8 These factors play a large role in determining levels of concern, worry, anger, anxiety, fear, hostility, and outrage, which in turn can significantly change attitudes and behavior.…”
Section: The Risk Perception Modelmentioning
confidence: 99%
“…We conduct the first longitudinal analysis on a pan-European level, investigating whether differences in terrorism risk are reflected on terrorism perception, motivated by the Bayesian framework (Viscusi and O'Connor 1984;Viscusi 1985;Viscusi et al 1987;Rogers 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they found an influencing link between education level and attitude. Significantly, regarding experience, risk perception is derived from an overall experience level that rarely includes experience for the risk in question (Rogers, 1997). Realistic risk perception occurs when people have indirect or direct experience with the risks involved; otherwise, they must rely on other factors (Sjöberg, 2000).…”
Section: Amount Of Controlmentioning
confidence: 99%
“…If media or printed information fails, then using face-to-face communication may be the most effective (Lester, 2000). Ultimately, the risk communication goal should be to garner and incorporate public risk perception information into the risk assessment decisions of the organization utilizing SMS (Rogers, 1997).…”
Section: Communicationmentioning
confidence: 99%